2015
DOI: 10.30552/ejihpe.v1i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Apoyo familiar en mayores institucionalizados

Abstract: Los cambios sociales, eventos vitales y dificultades que acompañan al envejecimiento, pueden declinar en situaciones de soledad, y en el peor de los casos, de aislamiento. En casos de institucionalización, el efecto atenuante que tiene el apoyo familiar, puede verse incrementado ante la necesidad de hacer frente a una nueva etapa como la vejez. El objetivo de este estudio es analizar la frecuencia y el tipo de contactos familiares que mantienen en residencia, así como su grado de satisfacción al respecto. Todo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Another similarity established in the samples of both countries states that of all relatives, sons/daughters represent the largest proportion, which indicates that they are the main source of support for senior living in nursing homes, and this seems to be common in other cultures as well ( Dorado et al., 2015 ; Molero et al., 2015 ; Sansoni et al., 2013 ; Silva et al., 2014 ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Another similarity established in the samples of both countries states that of all relatives, sons/daughters represent the largest proportion, which indicates that they are the main source of support for senior living in nursing homes, and this seems to be common in other cultures as well ( Dorado et al., 2015 ; Molero et al., 2015 ; Sansoni et al., 2013 ; Silva et al., 2014 ).…”
Section: Discussionmentioning
confidence: 95%
“…This aspect is also consistent with the fact that in old age, social networks are reduced and largely consolidated in the family ( Riquelme-Marín et al., 2010 ), as well as with that reported regarding the composition of the social networks of senior residents at HRNHs, both in Spain and Colombia ( Zumalde, 1994 ). Evidence showed that older adults living in this type of retirement home seem to have sufficient family support networks ( Clos and Grossi, 2016 ; Molero et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Por otro lado, estudios que se han concentrado en población institucionalizada sostienen que el apoyo social que proveen los familiares es fundamental para que los adultos mayores perciban de manera positiva la salud mental (Cardona-Arango, Estrada-Restrepo, Chavarriaga-Maya, Segura-Cardona, Ordoñez-Molina y Osorio-Gómez, 2010;Molero, Pérez-Fuentes, Gázquez y Scalvo, 2011). Del mismo modo, se identifican factores como: experimentar bienestar psicológico, participar en espacios sociales (Cardona-Arias, Álvarez-Mendieta y Pastrana-Restrepo, 2014, Molina, Meléndez y Nava-[102] Maira Alejandra González-Gaviria, Diana Marcela Bedoya-Gallego DOI: https://doi.org/10.17533/ udea.rp.v11n2a04 rro, 2008), experimentar autonomía (Guerrero-Martelo, Galván y Vázquez, 2015;, realizar actividad física, estar en un ambiente seguro (Vitorino, Paskulin y Vianna, 2012), experimentar plenitud espiritual, cuidar de sí (Melguizo-Herrera et al, 2014), conservar y compartir recuerdos y tener una actitud positiva (Flecha, 2015).…”
unclassified